Message Design of Printed and Digital Material to Meaningful Learning - Rahmi, Ulfia; Azrul, Azrul (AT-TA'LIM, 2021)
This article reports on research a message design of printed and digital message in Learning Theory course at Universitas Negeri Padang (UNP). Survey was conducted to collect data on the utilization of instructional materials by students who ware active in the semester in January-June. The results indicated that the print instructional materials written by lecturers have started to consider the design principles message, but still needs to be improved. That principle has not been carried out for digital teaching materials. Digital teaching materials need to be developed to familiarize students studying in 21st century environments by optimizing the campus e-learning facility to be able to perform generative learning, and meaningful learning